Size and Operating Profitability Portfolio Returns and Return Premia in Japan—A Tour d’horizon - Chikashi Tsuji (Journal of Management Research, 2024)
This study examines the Japanese equity returns and return premia by focusing on firm size- and corporate operating profitability-sorted portfolios over the period from 1990 to 2020. As a result of our explorations, this study derives the following much beneficial findings. (1) The effects of corporate operating profitability and firm size are generally continuously seen in the Japanese equity market. More specifically, (2) the size effect is much stronger in our latter half sub-period; while the operating profitability effect is similarly seen in both our former half and latter half sub-periods. Furthermore, (3) we stress that this study employs the data in US dollars, and calculates several key statistics and measures for not only our full sample period but also many different sub-periods, in which economic and business circumstances are much different. Therefore, for both Japanese and international equity investors, our findings shall be highly useful for enriching and furthering the understanding of returns and return premia of Japanese equity portfolios.